The Impact of Covid-19 on MSMEs Financing in Indonesia: The Role of Mudharabah and Musharakah - Widyanata, Fera; Syathiri, Ahmad; ., Dwirini (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2022)
One of the economic sectors hardest hit by the Covid-19 in Indonesia is MSMEs. During the Covid-19 pandemic, business capital assistance is urgently needed by MSMEs to keep running. Mudharabah and musharakah are Islamic banking financing products explicitly aimed at business needs and investment in the real sector, such as MSMEs. Therefore, a more in-depth quantitative analysis is needed regarding the role of mudharabah and musharakah contracts on MSMEs financing during the Covid-19 using panel data regression techniques, with a monthly observation period from March 2020 to May 2021 for all Islamic banking in Indonesia. With the Fixed Effect Model approach, it was found that the mudharabah and musharakah contracts statistically had no significant effect on MSMEs financing during the Covid-19. The conclusion is that during the Covid-19, there was an increase in MSMEs financing with mudharabah contracts, but it was not significant. In contrast, the musharakah contract did not increase the contribution to MSMEs financing.